The Influence Of Giving Ginger Water On The Pain Of Dysmenorroa In Adolescent Women - Desiana, Desiana; Utami, Vida Wira; Nurliani, Nurliani; Sary, Lolita (JKM (Jurnal Kebidanan Malahayati), 2024)
Background: Dysmenorrhea is a symptom of pain or discomfort in the lower abdomen during menstruation so that it can interfere with daily activities, which is most often found in young and reproductive women. In Indonesia, dysmenorrhea is also a complaint that is often found in young women. In Indonesia, the incidence of menstrual pain in 2018 was 107,673 people (64.24%), consisting of 59,671 people (54.89%) experiencing primary menstrual pain and 9,496 people (9.36%) experiencing secondary menstrual pain. Research objective: To know the effect of giving ginger water on dysmenorrheal pain in young women at Tri Bhakti Vocational School, Abung Tengah District, North Lampung Regency in 2023Research Methods: The type of research used was pre-experimental with a one-group pre-test and post- test design approach. Research population The population in this study were all young women at Tri Bhakti Vocational School who experienced dysmenorrhea as many as 53 people. The sample in this study amounted to 23 people. Sampling technique purposive sampling Analysis using the Wilcoxon test.The results of the study: The average level of dysmenorrhea before administration of ginger decoction (zingibers officinale) in female adolescents was 4.43 with a standard deviation of 0.662. A minimum of 3 and a maximum of 5. The average rate of dysmenorrhea after administration of ginger decoction (zingibers officinale) in young women is 2.39 with a standard deviation of 0.789. Conclusion Minimum 1 and maximum 3 There is a significant difference between giving ginger concoction to the level of dysmenorrhea pain in young women at Tri Bhakti Vocational School, Abung Tengah District, North Lampung Regency, p value 0.000. Suggestion  that the findings of this study can be a solution in overcoming dysmenorrhea by using a type of non-pharmacological therapy, namely giving red ginger water. Keywords : dysmenorrhea, ginger, young women ABSTRAK : PENGARUH PEMBERIAN AIR JAHE TERHADAP NYERI DISMENORROA PADA REMAJA WANITA Latar Belakang: Dismenore merupakan gejala nyeri atau rasa tidak nyaman pada perut bagian bawah saat menstruasi sehingga dapat mengganggu aktivitas sehari-hari, yang paling sering dijumpai pada wanita usia muda dan reproduktif. Di Indonesia, dismenore juga menjadi keluhan yang sering dijumpai pada remaja putri. Di Indonesia, angka kejadian nyeri haid pada tahun 2018 sebanyak 107.673 orang (64,24%), terdiri dari 59.671 orang (54,89%) mengalami nyeri haid primer dan 9.496 orang (9,36%) mengalami nyeri haid sekunder. Tujuan Penelitian: Untuk mengetahui pengaruh pemberian air jahe terhadap nyeri dismenore pada remaja putri di SMK Tri Bhakti Kecamatan Abung Tengah Kabupaten Lampung Utara Tahun 2023Metode Penelitian: Jenis penelitian yang digunakan adalah pre-eksperimental dengan pendekatan one group pre-test and post-test design. Populasi Penelitian Populasi dalam penelitian ini adalah seluruh remaja putri SMK Tri Bhakti yang mengalami dismenore sebanyak 53 orang. Sampel dalam penelitian ini berjumlah 23 orang. Teknik pengambilan sampel purposive sampling Analisis menggunakan uji Wilcoxon.Hasil penelitian: Rata-rata tingkat kejadian dismenore sebelum pemberian rebusan jahe (zingibers officinale) pada remaja putri adalah 4,43 dengan standar deviasi 0,662. Minimal 3 dan maksimal 5. Rata-rata kejadian dismenore setelah pemberian rebusan jahe (zingibers officinale) pada remaja putri adalah 2,39 dengan standar deviasi 0,789.Kesimpulan Minimal 1 dan Maksimal 3 Terdapat perbedaan yang signifikan pemberian ramuan jahe terhadap tingkat nyeri dismenore pada remaja putri di SMK Tri Bhakti Kecamatan Abung Tengah Kabupaten Lampung Utara p value 0,000. Saran hasil penelitian ini dapat menjadi solusi dalam mengatasi dismenore dengan menggunakan jenis terapi non farmakologi yaitu pemberian air jahe merah. Kata Kunci : dismenore, jahe, remaja putri